2018
DOI: 10.1039/c7ra13597a
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of nano-sized silver colloids stabilized by nitrogen-containing polymers: the key influence of the polymer capping

Abstract: Synthesis of stable silver colloids was achieved using nitrogen-containing polymers acting simultaneously as a reducing and stabilizer agent. The polymers polyethyleneimine (PEI), polyvinylpyrrolidone (PVP) and poly(2-vinyl pyridine)-b-poly(ethylene oxide) (PEO-b-P2VP) were used in the procedures. The influence of the surface chemistry and chemical nature of the stabilizer on the cytotoxicity and antimicrobial properties have been evaluated. The produced nanomaterials were found to be non-toxic up to the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 51 publications
2
22
1
Order By: Relevance
“…Silver ions were also reported to induce reactive oxygen species in bacteria which leads to the destruction of the bacterial cell ( Meena et al, 2013 ; Shaikh et al, 2019 ). It has been reported that the antimicrobial activity of Ag-NPs was enhanced by the combination of polymer even at low concentrations ( Chen et al, 2016 ; Abbas et al, 2018 ; Batista et al, 2018 ). Chitosan, a cationic polysaccharide was used along with Ag-NPs to improve the antimicrobial properties of NPs ( Abdelgawad et al, 2014 ).…”
Section: Role Of Nanotechnology In Crop Protectionmentioning
confidence: 99%
“…Silver ions were also reported to induce reactive oxygen species in bacteria which leads to the destruction of the bacterial cell ( Meena et al, 2013 ; Shaikh et al, 2019 ). It has been reported that the antimicrobial activity of Ag-NPs was enhanced by the combination of polymer even at low concentrations ( Chen et al, 2016 ; Abbas et al, 2018 ; Batista et al, 2018 ). Chitosan, a cationic polysaccharide was used along with Ag-NPs to improve the antimicrobial properties of NPs ( Abdelgawad et al, 2014 ).…”
Section: Role Of Nanotechnology In Crop Protectionmentioning
confidence: 99%
“…In other case, the reducing substance can play the role of a reducing agent and a ligand, which forms a complex compound with the available metal ion. It is typical for reducing polymers including a nitrogen atom as heteroatom, e.g., poly(vinylpyrrolidone) (PVP), polyethylenimine (PEI), or polyaniline (PANI) [168][169][170][171][172][173][174]. Such a formation of a complex compound is widely applied in practice for the tailored preparation of metal nanoparticles.…”
Section: Preparation Of Metal Nanoparticles By Chemical Reduction: Romentioning
confidence: 99%
“…Polymer capping has been studied for stabilizing nanomaterials at small sizes [18–19] . Likewise, some polymer have been used as capping agents to control the size of PB NPs, such as polyvinylpyrrolidone (PVP), which was used to encapsulate the PB NPs during synthesis to form stable core‐shell PB@PVP NPs [20] .…”
Section: Introductionmentioning
confidence: 99%